MANEJEMEN REKRUTMEN PENDIDIK DI MTS AL KHAIRIYAH SIDOMULYO KECAMATAN SIDOMULYO KABUPATEN LAMPUNG SELATAN - sularsih, sularsih (UNISAN JURNAL, 2024)
The recruitment process is very important to obtain effective recruitment results. Recruitment is carried out according to school needs. This research aims to determine the management of teaching staff recruitment at MTs Al Khairiyah. The research method used in this research is a qualitative descriptive method with data collection techniques carried out through interviews, observation and documentation studies. Careful planning is carried out by the teaching staff recruitment committee. The recruitment of teaching staff is carried out by the recruitment committee. Effective and conducive supervision carried out by officers supervising the recruitment of teaching staff. Evaluation of the recruitment of teaching staff by the chairman of the recruitment committee by re-examining the requirements of the applicant pool. The results of the recruitment process are quantitative: the recruitment achievement carried out by MTs Al Khairiyah reached 23 teaching staff, and qualitatively: the recruitment of teaching staff is in accordance with the needs of MTs Al Khairiyah; namely getting professional teaching staff.